C-reactive protein and drain amylase accurately predict clinically relevant pancreatic fistula after partial pancreaticoduodenectomy. (April 2020) - Mintziras, Ioannis; Maurer, Elisabeth; Kanngiesser, Veit; Bartsch, Detlef Klaus
Abstract: Backround: C-reactive protein (CRP) and procalcitonin (PCT) have shown to be reliable predictors of inflammatory complications and anastomotic leak after colorectal surgery. Their predictive value after partial pancreaticoduodenectomy (PD) remains unclear. Materials and methods: All consecutive pancreaticoduodenectomies (2009–2018) at our hospital were included. Drain amylase was evaluated on postoperative day (POD) 1, serum CRP and PCT were evaluated on POD 1–3. Receiver-operating characteristics curves were performed and significant cut-off values were tested using logistic regression. Results: Among 188 patients who underwent partial PD, clinically relevant pancreatic fistulas (POPF) occurred in 30 (16%) patients, including 20 (10.6%) with Grade B and 10 (5.3%) patients with Grade C. Postoperative complications (Clavien-Dindo ≥ III) were reported in 46 (24.5%) patients, including Grade IIIa in 16 (8.5%), IIIb in 18 (9.6%), IVa in 3 (1.6%), IVb in 2 (1.1%) and V in 7 (3.7%) patients. Drain amylase on POD 1 showed the largest area under the curve (0.872, p < 0.001), followed by CRP (0.803, p < 0.001) and PCT on POD 3 (0.651, p < 0.011). Drain amylase on POD 1 > 303 U/l (OR 0.045, 95% CI 0.010–0.195, p < 0.001), CRP > 203 mg/l (OR 0.098, 95% CI 0.041–0.235, p < 0.001) and PCT > 0.85 μg/l (OR 0.393, 95%CI 0.178–0.869, p = 0.02) were significant predictors of relevant POPF in the univariate analysis. CRP > 203 mg/l (OR 0.098, 95% CI 0.024-0.403, p = 0.001) and drain amylase > 303 U/l (OR 0.064, 95% CI 0.007-0.554, p = 0.01) remained independent predictors in the multivariable analysis. The combination of drain amylase on POD 1 and CRP on POD 3 had a sensitivity and specificity of 87.4% and 90.9% to predict relevant POPF. Conclusion: Drain amylase on POD 1 and CRP on POD 3 can accurately predict clinically relevant POPF after partial pancreaticoduodenectomy. The accuracy of PCT on POD 3 is limited. Highlights: CRP, procalcitonin on postoperative days (POD) 1–3 and drain amylase on POD 1 were evaluated among 188 patients undergoing partial pancreaticoduodenectomy. Drain amylase on POD 1 > 303 U/l (OR 0.045, 95% CI 0.010–0.195) and CRP > 203 mg/l (OR 0.098, 95% CI 0.041–0.235) were independent predictors of clinically relevant postoperative pancreatic fistula. The combination of CRP on POD 3 and drain amylase on POD 1 had a sensitivity and specificity of 87.4% and 90.9% to predict relevant POPF.